General physical fitness of servicemen as the main element of increasing military-special training - Oleh Nebozhuk; Oksana Matveiko; Ivan Pylypchak; Ihor Lototskyi; Svitlana Indyka; Natalia Bielikova (Jan Długosz University in Częstochowa, 2023)
With the beginning of Russia's armed aggression against Ukraine, the Armed Forces of Ukraine need significant reforms and improvements both in technical rearmament and reorganization of the administrative structure in accordance with the requirements of professionalization and the transition of the Armed Forces to staffing on a voluntary basis. The training of any serviceman cannot be complete if it is limited only to knowledge of the use of military equipment and weapons and the ability to use them. An integral condition for the successful completion of professional tasks is the ability of each serviceman to make the most of all the power of military equipment in the shortest possible time. An urgent issue is the improvement of programs for physical training of servicemen, which in the future will ensure the quality of tasks in accordance with the purpose and performance of tasks. The purpose of this study was to analysis and improvement of the level of dynamics of the general physical fitness of servicemen taking into account purposeful performance of tasks. The research has shown that, at all stages of the experiment, the level of general physical fitness of contract servicemen is worse than that of civilian youth cadets (t = 2,25-2,66; р < 0.05). It was revealed that in both groups the dynamics of indicators of general physical fitness is posi- tive, but there is no significant difference, which indicates the lack of effectiveness of the current program of physical fitness, regardless of the category of cadets, effectiveness of the current program of physical fitness, or the category of cadets.